Use of cost accounting in cost management - Lew, Grzegorz (Wykorzystanie rachunków kosztów w zarządzaniu kosztami, 2019)
Cost accounting is the basic accounting tool used to optimize costs in companies. The evolution of accounting also concerned changes in cost accounting. In the second half of the twentieth century many new cost accounting methods were created, the main task of which was to support managers in increasing the financial performance of companies. The aim of the article is to analyze the possibility of using different cost accounting by companies to manage their customers’ costs. The main thesis is that companies are aware of the possibility of using management accounting tools to manage their customers’ costs. In the article literature studies and the results obtained from the responses to the questions in the questionnaire were used. The study was conducted among 71 companies in south-eastern Poland. Based on this research, it was determined that, despite the possibility of using different cost accounting methods, Polish companies prefer to use traditional cost accounting to manage their costs
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 161-171
Keywords: cost accounting; finance; management accounting; cost management; rachunek kosztów; finanse; rachunkowość zarządcza; zarządzanie kosztami